A First Approach to the Implicit Measurement of Happiness in Latin America Through the Use of Social Networks - Mochón, Francisco; Sanjuán Martínez, Óscar (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
This research paper can be classified as pertaining to the group of empirical studies that try to measure subjective well-being. The article presents as its greatest contributions the use of a subjective measurement of well-being based on social networks for the Latin American setting, as well as its comparative analysis with another traditional method.
Keywords: happiness; subjective well-being; social networks; twitter; latin America; latinobarómetro; IJIMAI